ROLE OF PHYSICAL ACTIVITY IN THE MULTIDISCIPLINARY MANAGEMENT OF CYSTIC FIBROSIS: A LITERATURE REVIEW - Weronika Worosz; Diana Wisz; Filip Maciej Huzarski; Katarzyna Adrianna Tryniecka; Katarzyna Maria Turek; Alicja Zań (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cystic fibrosis (CF) is a multisystem genetic disorder in which progressive pulmonary disease remains the leading cause of morbidity and mortality. Advances in pharmacological therapy, particularly CFTR modulators, have transformed the clinical landscape; however, non-pharmacological strategies—especially structured physical activity (PA)—remain essential for optimising long-term outcomes. This review synthesises current evidence on the physiological basis, clinical benefits, safety considerations, and practical implementation of PA as part of multidisciplinary CF management. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and Web of Science for peer-reviewed articles published between 2020 and 2025. Search terms included cystic fibrosis; physical activity; exercise training; pulmonary rehabilitation; multidisciplinary care. Randomised controlled trials, systematic reviews, meta-analyses, and relevant clinical guidelines were included. Results: Evidence consistently shows that regular physical activity improves exercise capacity, enhances mucus clearance, and contributes to stabilizing or improving selected parameters of lung function in people with cystic fibrosis. Aerobic, endurance, combined, and inspiratory muscle training provide complementary benefits for cardiovascular fitness, muscle strength, bone health, and mental well-being. Home-based programs, supported by telemedicine, offer comparable results to in-person training while reducing the risk of infection. Regular physical activity is often hindered by disease symptoms, limited access to appropriate sports facilities, and psychosocial limitations. However, there are facilitating factors, such as personalized exercise recommendations, support from an interdisciplinary team, and digital monitoring technologies, which enable ongoing patient engagement. Conclusions: Physical activity is a safe, effective, and versatile component of multidisciplinary CF care, offering physiological, functional, and psychosocial benefits that complement pharmacological and airway clearance therapies. Integrating tailored exercise interventions into routine management should be prioritised to maximise health outcomes and quality of life in this population.